OBSERVATIONS ON THE SPAWNING OF THE MAJOR CARPS AT A FISH-FARM IN THE PUNJAB - Khanna, Dharam Vir (Indian Journal of Fisheries, 2016)
It is of prime importance for the development of Indian fisheries to acquire thorough knowledge of the breeding habits of the Indian carps and of the most favourable conditions under which they spawn. It was with this aim that the Council of the National Institute of Sciences of India arranged a symposium on the ’ Factors Influencing the Spawning of Indian Carps’ in 1945. Dr. Hora, winding up the symposium, laid stress onâ€”(i) flooded condition of a river or a tank, (ii) high pH and oxygen content value of water and (iii) temperature, as the factors of considerable importance.